Study on the Development of Indonesia and Malaysia Shallot Imports - Umar Fachry Manullang; Mailina Harahap; Ahmad Zairy Bin Zainol Abidin (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2025)
This study analyses shallot import trends in Indonesia and Malaysia from 2010 to 2023. Indonesia, while a net exporter, experiences fluctuating imports, primarily due to seasonal production variations and occasional supply shortfalls. Malaysia, lacking significant domestic production, consistently relies heavily on imports, primarily from India. The study utilises a descriptive qualitative method, incorporating both primary (interviews, observations) and secondary data (government reports, trade statistics). Key findings highlight Brebes, Indonesia, as a major shallot production centre, employing technologies like Controlled Atmosphere Storage (CAS) to extend shelf life. Data mining techniques, specifically linear regression, are used to predict shallot yields based on factors like land area, fertiliser use, and labour. Despite improved productivity per hectare, total production in Brebes fluctuated, indicating challenges in maintaining production scale. Malaysia's shallot import dependence is underscored by its reliance on 24 countries, with India being the largest supplier. MARDI's efforts to cultivate local shallot varieties represent a step towards self-sufficiency. The study examines factors driving imports, including resource limitations, consumption needs, competitive advantages, and economic policies. The instability of shallot production, particularly during the rainy season, contributes to price fluctuations. The analysis concludes by emphasising the need for both countries to enhance domestic production through technological advancements, improved cultivation techniques, and supportive government policies to reduce import dependence and stabilise prices.